CASE STUDIES OF CROSS-BORDER CO-OPERATION IN EUROPEAN TOURISM – PERSPECTIVES AND CHALLENGES FOR THE CROSS-BORDER REGION BUCOVINA/OBLAST TSCHERNIWZI - HEIKE BÄHRE (USV Annals of Economics and Public Administration, 2016)
The article focuses on success factors and management models in destination management for cross-border co-operation in tourism. The method is based on literature research, case-studies in European cross-border-regions and descriptive.